Pengenalan Teknologi Artificial Intellegence Pada Panti Asuhan Al Hidayah Padang - Hadi Syahputra; Musli Yanto; Selvi Zola Fenia (Jurnal Pengabdian Masyarakat Dharma Andalas, 2026)
The rapid development of information technology in the era of the Industrial Revolution 4.0 has had a major impact on various aspects of life, including the world of education and the daily lives of the younger generation. One of the most prominent technologies today is Artificial Intelligence (AI). Understanding of AI is still very limited, especially among teenagers who come from economically disadvantaged backgrounds, including children in orphanages. Children at the AL-Hidayah Padang Orphanage often face limited access to information and cutting-edge technology, including knowledge about AI. As part of the role of the tri dharma of higher education, lecturers have a responsibility to participate in educating the nation's life through community service activities. Through the PKM program entitled "Introduction to Artificial Intelligence Technology at the Al Hidayah Padang Orphanage", lecturers and students want to make a real contribution by introducing the basic concepts of AI to foster children and the orphanage's guidance. This socialization is expected to spark curiosity, enthusiasm for learning technology, and open their insights to future opportunities in the digital and artificial intelligence fields. This activity aims not only to provide a theoretical understanding of AI, but also to provide practical and interactive experiences through simple demonstrations, AI-based educational games, and inspiring discussions. With a fun and easy-to-understand approach, this activity is expected to be the first step in building technological literacy among the foster children and their caregivers at the Al Hidayah Orphanage in Padang.